Evaluation of in vitro and in vivo immunostimulatory activities of poly (lactic-co-glycolic acid) nanoparticles loaded with soluble and autoclaved Leishmania infantum antigens: A novel vaccine candidate against visceral leishmaniasis - Abamor, Emrah Sefik; Allahverdiyev, Adil; Tosyali, Ozlem Ayse; Bagirova, Melahat; Acar, Tayfun; Mustafaeva, Zeynep; Derman, Serap (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
Objective: To prepare and characterize poly lactic-co-glycolic acid (PLGA) nanoparticles loaded with soluble leishmanial antigen or autoclaved leishmanial antigen and explore in vitro and in vivo immunogenicity of antigen encapsulated nanoparticles. Methods: Water/oil/water double emulsion technique was employed to synthesize PLGA nanoparticles, and scanning electron microscopy, Fourier transform infrared spectroscopy and Zeta-potential measurements were used to identify the characteristics of nanoparticles. Cytotoxicity of synthetized nanoparticles on J774 macrophage were investigated by MTT assays. To determine the in vitro immunostimulatory efficacies of nanoparticles, griess reaction and ELISA was used to measure the amounts of NO and cytokines. During the in vivo analysis, Balb/c mice were immunized with vaccine formulations, and protective properties of nanoparticles were measured by Leishman Donovan unit in the liver following the infection. Cytokine levels in spleens of mice were determined by ELISA. Results: MTT assay showed that neither soluble leishmanial antigen nor autoclaved leishmanial antigen encapsulated nanoparticles showed cytotoxicity against J774 macrophage cells. Contrary to free antigens, both autoclaved leishmanial antigen-nanoparticle and soluble leishmanial antigen-nanorrarticle formulations led to a 10 and 16-fold increase in NO amounts by macrophages, respectively. Leishman Donovan unit calculations revealed that soluble leishmanial antigen-nanoparticles and autoclaved leishmanial antigen-nanoparticles yielded 52% and 64% protection against visceral leishmaniasis in mouse models. Besides, in vitro and in vivo tests demonstrated that by increasing IFN-gamma and IL-12 levels and inhibiting IL-4 and IL-10 secretions, autoclaved leishmanial antigen-nanoparticles and soluble leishmanial antigen-nanoparticles triggered Thi immune response. Conclusions: Both autoclaved leishmanial antigen-nanoparticles and soluble leishmanial antigen-nanoparticles formulations provide exceptional in vitro and in vivo immunostimulatory activities. Hence, PLGA-based antigen delivery systems are recommended as potential vaccine candidates against visceral leishmaniasis.
Keywords: Visceral leishmaniasis; Vaccine; Delivery; Immunostimulant; Poly lactic-co-glycolic acid (PLGA); Nanoparticle; NITRIC-OXIDE PRODUCTION; CPG ODNS INDUCE; PLGA NANOPARTICLES; MURINE MODEL; PROTECTION; Public, Environmental & Occupational Health; Tropical Medicine